Why We Dance: A Philosophy of Bodily Becoming. By K. LaMothe - Carp, Richard M. (Body and religion, 2018)
Why We Dance: A Philosophy of Bodily Becoming By K. LaMothe (2015) New York: Columbia University Press, 300pp.